Evaluasi dan Re-Mapping APAR di Lingkungan Gedung Perkantoran PLN UID Jawa Timur - Prastya, Deny Nurcahyo Hari; Martiana, Tri; Parlan (Indonesian Society of Applied Science, 2025)
This research aims to evaluate and re-map the Portable Fire Extinguishers (PFE) in the office buildings of PLN UID East Java. The method employed is a descriptive observational approach, gathering primary data through direct observation and structured interviews, supplemented by secondary data from document reviews. The findings reveal a gap between fire safety standards and actual conditions, such as improper PFE placement, unclear expiration dates, and an uneven distribution of PFE across buildings. Risk analysis identifies hazards from these issues, including delayed fire response and potential failure of PFE during emergencies. Calculating PFE needs based on Permenakertrans Regulation No. 04/MEN/1980 and NFPA-10 edition 2022 generates recommendations for redistributing PFE. Based on these calculations, three buildings (C, F, I) are found to have an excess of 13 PFE, while four buildings (A, B, D, E) are short by 9 PFE. The recommendation suggests transferring 11 PFE from Building F: 4 PFE to Building A, 3 PFE to Building B, and 2 PFE each to Buildings D and E. This redistribution ensures the correct number of PFE in each building, enhancing fire safety management in PLN UID Jawa Timur office buildings. This action aims to align the PFE distribution with safety requirements.